Introduction to plant cryopreservation - Panis, Bart (2025)
Presentation at webinar organized by the CGIAR Genebank Accelerator "Advancing Molecular Characterization of Clonal, Legume, and Cereal Crops" ; Objective: Deliver a conceptual foundation in molecular characterization, cryopreservation, bioinformatics, and data sharing for Clonal, Legume, and Cereal crops, preparing participants for a hands-on course and fostering a Community of Practice. The agenda addresses survey findings (e.g., crop priorities, 37.9% lack DNA extraction capacity, 69.0% bioinformatics skills gap) and ensures accessibility for participants from Europe, Africa, Latin America, and beyond. Week 2: Cryopreservation and Advanced Molecular Characterization (8-12 Sept) Objective: Deepen understanding of molecular characterization with genotyping platforms and reference genomes, and introduce cryopreservation techniques.